Influence of the Period of Abstinence on Semen Quality in a Patient with Systemic Lupus Erythematosus: A Case Report and Review of the Literature - Tarah H. B. Waters; Carol Pui Shan Chan; Tin Chiu Li; David Yiu Leung Chan (Case Reports in Rheumatology)
Systemic lupus erythematosus (SLE) is a chronic inflammatory disease that can affect fertility. There is currently little information regarding the semen profile of males with SLE. Moreover, there is no consensus on an appropriate period of sexual abstinence for semen analysis and on the use of DNA fragmentation assay, together with multiple semen analyses to document the semen profile in this clinical population. In this case report, multiple semen analyses, with DNA fragmentation assays, were performed for a male with SLE undergoing fertility treatment at our andrology unit. A 4-day period of abstinence improved the semen concentration, total sperm count, total progressive motile sperm, and sperm morphology, with minimal DNA fragmentation. In conclusion, multiple semen analyses obtained after different periods of sexual abstinence, together with DNA fragmentation assays, may be useful to develop a semen profile for patients with SLE, providing information on the optimal abstinence period to yield the best semen quality for subsequent fertility treatment. For patients with fluctuating semen results, concomitant semen cryopreservation should be considered to preserve the better quality semen before starting assisted reproductive technologies if pregnancy is planned in the future.